Economic Impact of Renewable Energy on Sustainable Development in Saudi Arabia - Benlaria, Houcine; Hamid Hamad, Abu Alhassan Jumaa (International Journal of Energy Economics and Policy, 2022)
This paper studies the asymmetric relationship between renewable energy consumption and economic growth incorporating capital and labor for the case of Saudi Arabia during the period 1990-2019. The nonlinear lagged cointegration (NARDL) model is applied to examine the asymmetric cointegration between the variables. The results indicate that there is an asymmetric relationship between the variables considered. The negative labor shock improves economic growth, while a positive shock reduces (increases) economic growth in the short term. Therefore, policies to promote economic growth, such as the need to improve the quality of financial development and preserve fiscal sustainability, are crucial to improve the renewable energy sector in Saudi Arabia. At the same time, it is essential that the renewable energy sector must also be oriented towards productive development projects.